The Oral, Gut Microbiota and Cardiometabolic Health of Indigenous Orang Asli Communities - Yeo, Li-Fang; Lee, Soo Ching; Palanisamy, Uma Devi; Khalid, BAK.; Ayub, Qasim; Lim, Shu Yong; Lim, Yvonne AL.; Phipps, Maude Elvira (Frontiers in Cellular and Infection Microbiology, 2022)
The Orang Asli (OA) of Malaysia have been relatively understudied where little is known about their oral and gut microbiomes. As human health is closely intertwined with the human microbiome, this study first assessed the cardiometabolic health in four OA communities ranging from urban, rural to semi-nomadic hunter-gatherers. The urban Temuan suffered from poorer cardiometabolic health while rural OA communities were undergoing epidemiological transition. The oral microbiota of the OA were characterised by sequencing the V4 region of the 16S rRNA gene. The OA oral microbiota were unexpectedly homogenous, with comparably low alpha diversity across all four communities. The rural Jehai and Temiar PP oral microbiota were enriched for uncharacterised bacteria, exhibiting potential for discoveries. This finding also highlights the importance of including under-represented populations in large cohort studies. The Temuan oral microbiota were also elevated in opportunistic pathogens such as Corynebacterium, Prevotella, and Mogibacterium, suggesting possible oral dysbiosis in these urban settlers. The semi-nomadic Jehai gut microbiota had the highest alpha diversity, while urban Temuan exhibited the lowest. Rural OA gut microbiota were distinct from urban-like microbiota and were elevated in bacteria genera such as Prevotella 2, Prevotella 9, Lachnospiraceae ND3007, and Solobacterium. Urban Temuan microbiota were enriched in Odoribacter, Blautia, Parabacetroides, Bacteroides and Ruminococcacecae UCG-013. This study brings to light the current health trend of these indigenous people who have minimal access to healthcare and lays the groundwork for future, in-depth studies in these populations.